(untitled) (Jurnal Ilmiah dr. Aloei Saboe, 2023)
This study aims to determine the effectiveness of reporting medical record data before and after using the Hospital Management Information System at RSUD Dr. M.M Dunda Limboto. The effectiveness of data reporting is seen from the accuracy of the data and the accuracy of returning medical record files. The research method used is quantitative research using a comparative approach. Collecting data in this study using a questionnaire, observation and documentation. The sampling technique used is a total sampling technique where the sample from the study amounted to 32 respondents. The results of this study indicate that there is a significant difference between the Manual Hospital Management Information System and the SIMGOS 2 Hospital Management Information System application in reporting medical record data. The average value obtained from the results of the manual paired sample t-test got a mean value of 78.00 while the Hospital Management Information System application SIMGOS 2 got a mean value of 133.80 from these results it can be concluded that the Hospital Management Information System application SIMGOS 2 is more effective compared to manual Hospital Management Information Systems.